دراسة تحليلية فنية واقتصادية لكفاءة بعض عناصر منظومة القدرة في السفينة - شلوف محمد (Latakia University Journal -Engineering Sciences Series, 2014)
تحسنت المؤشرات الفنية والاقتصادية لأغلب الشركات البحرية في الدول المتقدمة نتيجةً للتطبيق الدقيق للقواعد الفنية والإدارية السليمة لاستثمار سفنها، وخاصة بعد دخول مدونة الإدارة الفنية العالمية السليمة (ISM). وانطلاقاً من ذلك تمت دراسة آليات الاستثمار الفني في الشركات البحرية السورية للوقوف على الواقع الفعلي للاستثمار الفني، وسعياً للوصول إلى وضع أفضل، تمت دراسة معطيات من عدة شركات بحرية سورية وتقييمها، وتم التوصل لبعض النتائج التي نعتقد أن أخذها بالاعتبار سيؤدي إلى تحسين الظروف الفنية والاقتصادية والبيئية للاستثمار الفني للسفن السورية، وتقليل التوقفات الناتجة عن الأعطال في هذه السفن، وصولاً إلى سوية أعلى للاستثمار الفني وتحقيق نتائج اقتصادية أفضل. The technical and economical indexes of most maritime companies in developed countries have improved due to the strict application of the administrative and technical regulations in order to operate their ships, especially after the International Safety Management code (ISM) has come into force. With this in mind, this paper studies the mechanisms of technical operation in Syrian maritime companies in order to have a realization of the actual reality of technical operations, and also to reach a better status. Data from various Syrian maritime companies are collected and assessed, from which several results are obtained which, when taken into consideration, are believed to lead to improving the technical, economic, and environmental circumstances surrounding the technical operation of ships in Syria. They will also lead to lessening the stoppages that result from malfunctions in these ships, and ultimately reaching a higher level of technical operation and achieving superior outcomes.